Helminth-induced immune modulation in colorectal cancer: exploring therapeutic applications - Li, Hongyu; Shan, Chaojun; Zhu, Yunhuan; Yao, Xiaodong; Lin, Lijun; Zhang, Xiaofen; Qian, Yuncheng; Wang, Yuqing; Xu, Jialu; Zhang, Yijie; Li, Hairun; Zhao, Ling; et al. (Frontiers in Immunology, 2025)
Colorectal cancer is one of the most lethal tumors, posing a financial and healthcare burden. This study investigates how helminths and pre-existing diseases such as colitis, obesity, diabetes, and gut microbiota issues influence colon cancer development and prognosis. The immune system’s protective immunosuppressive response to helminth invasion minimizes inflammation-induced cell damage and DNA mutations, lowering the risk of colorectal cancer precursor lesions. Helminth infection-mediated immunosuppression can hasten colorectal cancer growth and metastasis, which is detrimental to patient outcomes. Some helminth derivatives can activate immune cells to attack cancer cells, making them potentially useful as colorectal cancer vaccines or therapies. This review also covers gene editing approaches. We discovered that using CRISPR/Cas9 to inhibit live helminths modulates miRNA, which limits tumor growth. We propose more multicenter studies into helminth therapy’s long-term effects and immune regulation pathways. We hope to treat colorectal cancer patients with helminth therapy and conventional cancer treatments in an integrative setting.